Graft Copolymerization of Methyl Methacrylate onto Rubber-Wood Fiber using H2 O2 and Fe2+ as an Initiator System - Abu-Ilaiwi, Faraj A.; Ahmad, Mansor; Ibrahim, Nor Azowa; Ab. Rahman, Mohamad Zaki (2003)
Methyl methacrylate (MMA) was successfully grafted onto rubber-wood fiber in a free-radical solution polymerization initiated by ferrous ion and hydrogen peroxide. The effects of the reaction parameters (reaction temperature, reaction period, influence of hydrogen peroxide, ferrous ammonium sulfate, and monomer concentrations) were investigated. The grafting percentage showed dependency on H2O2, Fe2+, and monomer concentrations, as well as reaction temperature and reaction period. The optimum reaction temperature was determined to be about 60°C and the reaction period was 60 min. The optimum concentration of H2O2 was 0.03M and optimum amounts of Fe2+ and MMA were 0.26 mmol and 2.36 × 10-2 mol, respectively. Poly(methyl methacrylate) (PMMA) homopolymer was removed from the graft copolymer by Soxhlet extractor using acetone. The presence of PMMA on the fiber was shown by FT-IR spectrpscopy and gravimetric analysis. © 2003 Wiley Periodicals, Inc.